HIGH SPEED SYSTEM USING VEDIC MATHEMATICS - A SURVEY (International Journal of Engineering Sciences & Management Research, 2015)
In the world of technology knowingly or unknowingly we use Vedic Sutra. Likewise, many Vedic sutras are used in multiplier unit of computer. It will give faster results, which is very much required in various applications like cryptographic algorithms, image processing applications. Traditional methods used for multiplication, division require more time as compared to Vedic methods. UrdhvaTiryagbhyam, Nikhilam sutra are used for multiplication purpose. It require less time, power and give results faster.